Diversity and roles of amenity trees at secretatriats' premises in Ibadan metropolis (2013)
This study evaluated the diversity and technical suitability of amenity planting of tree species inside the premises of the secretariats at Ibadan metropolis as well as the users’ perception of the trees. The trees in the seven secretariats in the metropolis were enumerated and identified to species level and were assessed for technical suitability for amenity use in work environment using selected attributes. Furthermore, forty questionnaires were administered to randomly selected respondents comprising staff in each secretariat. These questionnaires were used to examine the respondents’ perception on the benefits, threat and management of the amenity trees in the selected secretariats. A total of 260 questionnaires were retrieved and 20 were not returned. The data were analysed using descriptive statistics. The highest number of trees was found in the Oyo state secretariat (660 trees) while the lowest was in Ibadan South-West Local Government Secretariat (2 trees). A total of 30 tree species in 17 families were identified in all the secretariats. Tree density of less than one tree per square meter of land was observed for all the secretariats. Terminalia catappa was the predominant species found in 5 of the secretariats surveyed and Fabaceae was the most common family with 5 different species found during the study. Moreover, 30.8% identified the trio of cooling the environment, provision of shade and beautification of environment as a group of benefits derived from these trees. Furthermore, 69.6% suggested that more trees should be planted because the benefits outweighed the problems. Based on the traits of the identified trees in the secretariats’ premises, appropriate planting sites were recommended as suitable habitats for the trees. The study revealed that both the population and species diversity of trees in all the government secretariats with the exception of state secretariat were quite low. There is therefore a need to increase the population and diversity of the trees that will conform and be suitable for the built landscape of these premises.